Основные направления в решении вопросов производственного травматизма с тяжелыми последствиями - Капцов, В.А.; Овечкина, Ж.В. (Актуальні проблеми транспортної медицини, 2005)
A high level of occupational traumatism with fatalities among linesman composed a background of this problem study and work out of prophylactic measures for its decrease. The trials conducted resulted in the establishment that the majority of traumatism cases is the victims fault and depends on his personality psychological peculiarities. First they have learnt the personality of the died linesmen by indirect inquiring of his close persons. They have investigated 100 fatalities and inquired 300 persons according to special questionnaire. A questionnaire was done according to T. Lurie test in L.N.Sobchick's modification. The analysis of the questionnaires allowed to refer the died persons to the 5th type of interpersonal relations. The persons of such a type are diffident, they may be subordinated, they are careful and industrious, but they can neither gather themselves, nor react promptly to any danger. With the aim to prevent occupational traumatism with severe consequences they recommend to avoid to give employment of linesmen to the persons with such type of interpersonal relations.
On the basis of the results obtained they have worked out a technique for medical fitness examination. It included three tests those of Luscher, Ch. Spilberger-Khanin (the main ones) and Schubert's test as an additional one. These tests allow to identify the persons with 5th type of interpersonal